History and salvation in medieval Ireland - Boyle, Elizabeth (Cultural historian) (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"History and Salvation in Medieval Ireland explores medieval Irish conceptions of salvation history, using Latin and vernacular sources from c. 700 - c. 1200 CE which adapt biblical history for audiences both secular and ecclesiastical. This book examines medieval Irish sources on the cities of Jerusalem and Babylon; reworkings of narratives from the Hebrew Scriptures; literature influenced by the Psalms; and texts indebted to Late Antique historiography. It argues that the conceptual framework of salvation history, and the related theory of the divinely-ordained movement of political power through history, had a formative influence on early Irish culture, society and identity. Primarily through analysis of previously untranslated sources, this study teases out some of the intricate connections between the local and the universal, in order to situate medieval Irish historiography within the context of that of the wider world. Using an overarching biblical chronology, beginning with the lives of the Jewish Patriarchs and ending with the Christian apostolic missions, this study shows how one culture understood the histories of others, and has important implications for issues such as kingship, religion and literary production in medieval Ireland. This book will appeal to scholars and students of medieval Ireland, as well as those interested in religious and cultural history"--
OCLC-licensed vendor bibliographic record.
Keywords: Christianity -- Ireland; Salvation -- Christianity; Ireland -- Church history -- Middle Ages, 600-1500.; HISTORY / General